Enterobacter cloacae with a novel variant of ACT AmpC beta-lactamase originating from glaucous gull (Larus hyperboreus) in Svalbard - Literak, Ivan; Manga, Ivan; Wojczulanis-Jakubas, Katarzyna; Chroma, Magdalena; Jamborova, Ivana; Dobiasova, Hana; Sedlakova, Miroslava Htoutou; Cizek, Alois (Veterinary microbiology, 2014)
We aimed at Escherichia coli and Enterobacter cloacae isolates resistant to cephalosporins and fluoroquinolones and Salmonella isolates in wild birds in Arctic Svalbard, Norway. Cloacal swabs of little auks (Alle alle, n=215) and samples of faeces of glaucous gulls (Larus hyperboreus, n=15) were examined. Inducible production of AmpC enzyme was detected in E. cloacae KW218 isolate. Sequence analysis of the 1146 bp PCR product of the ampC gene from this isolate revealed 99% sequence homology with the blaACT-14 and blaACT-5 AmpC beta-lactamase genes. Four, respectively six of the identified single nucleotide polymorphisms generated amino acid substitutions in the amino acid chain. As the ampC sequence polymorphism in the investigated E. cloacae strain was identified as unique, we revealed a novel variant of the ampC beta-lactamase gene blaACT-23.
Keywords: Molecular Sequence Data; Sequence Analysis, DNA; Wildlife; Norsko; bakteriální léková rezistence; jednonukleotidový polymorfismus; Drug Resistance, Bacterial; Bacteria; Charadriiformes; polymerázová řetězová reakce; Amino Acid Substitution; Polymerase Chain Reaction; Antimicrobial resistance; substituce aminokyselin; DNA primery; Birds; Svalbard; Cloaca; Norway; Enterobacter cloacae; Bacterial Proteins; Base Sequence; sekvence nukleotidů; Escherichia coli; kloaka; zvířata; beta-laktamasy; beta-Lactamases; sekvenční analýza DNA; molekulární sekvence - údaje; DNA Primers; bakteriální proteiny; Polymorphism, Single Nucleotide; Animals